Influence of gravity on the skin thermal behavior: experimental study using dynamic infrared thermography. Issue 1 (22nd June 2012) - Ratovoson, Domoina; Jourdan, Franck; Huon, Vincent
<x xml:space="preserve">Abstract</x> Background/aim To better understand the thermomechanical behavior of the skin and its direct environment, we present an experimental study using dynamic infrared thermography. This experimental study aims to highlight quantitatively some effects of blood flow on the heat diffusion. Methods The originality of this research was to change the blood flow by using effects of gravity and to quantify the temperature changes. The experimental step consists of putting a cylindrical steel bar cooled or warmed on the skin of a human forearm and to measure the change of the temperature using an infrared camera. Measures have been recorded for different positions of the forearm. Result and conclusion We noted very clearly the influence of blood circulation in the veins on the diffusion of the temperature. The return to thermal balance is faster when the arm is in a horizontal position. Moreover, a comparative study of experimental cooling and warming showed a symmetrical thermal behavior for the skin under this type of thermal solicitations. This work provided to build a database that can be used for the validation of predictive thermal models of human skin.